Business Retention and Expansion (BRE) Programs: Characteristics of Successful BRE Programs - Henry M. Cothran (EDIS)
FE653, a 3-page fact sheet by Henry M. Cothran, is third in a series on establishing business retention and expansion (BRE) programs. It identifies and explores five of the most common characteristics of BRE programs recognized for their success. Published by the UF Department of Food and Resource Economics, April 2008.